Effects of malachite green on growth and tissue accumulation in pak choy (Brassica chinensis Tsen & Lee) - Matpang, Piyaporn; Sriuttha, Manop; Piwpuan, Narumol (Agriculture and Natural Resources, 2017)
Reuse for agricultural purposes of aquaculture wastewater containing high levels of nutrients can be integrated into a water management strategy, in order to conserve water and alleviate water pollution problems. However, rather than nutrients, some contaminants in aquaculture wastewater may pose detrimental effects on plants being nourished. This study assessed the growth and accumulation of toxic substances of Brassica chinensis in response to Malachite Green (MG)-contaminated water. Plant seedlings were hydroponically grown with MG at 1 mg/L, 2 mg/L or 4 mg/L under ambient air conditions in the laboratory for 4 wk. Growth parameters-the number of leaves, plant height, leaf length and width, root length and dry mass of the plantsdwere compared with plants grown without MG (control). The concentrations at 2 mg/L and 4 mg/L affected the growth of the plants as measured by leaf length, plant height and leaf width generally to a lesser degree than the control plants and those grown at 1 mg/L MG (p < 0.05). The roots of plants were clearly affected by MG (average root length = 14.00 ± 1.17 cm, 14.50 ± 3.91 cm, 7.17 ± 1.52 cm and 6.58 ± 0.94 cm for plants from the control and treatments with MG at 1 mg/L, 2 mg/L and 4 mg/L, respectively, p < 0.001). The dry mass of treated plants (average dry mass = 1.22 ± 0.48 g/plant, 1.17 ± 0.27 g/plant and 0.86 ± 0.17 g/plant for treatments of MG at 1 mg/L, 2 mg/L and 4 mg/L, respectively) were lower than that of control plants (1.80 ± 0.73 g/plant) (p < 0.001). The increase in the oxalate content in the plant shoots suggested that the plants may accumulate substances that could be harmful to human health. Based on these results, it is proposed that the integration of hydroponic plant production with MG-contaminated water at a concentration not exceeding 1 mg/L can be applied without any reduction in the productivity of B. chinensis; however, the accumulation of toxic substances in plant tissues still needs to be identified.